High sensitivity cavity ring down spectroscopy of N2O near 1.74 µm. (May 2019) - Bertin, Thibault; Mondelain, Didier; Karlovets, Ekaterina; Kassi, S.; Perevalov, Valery; Campargue, Alain
Highlights: High sensitivity cavity ring down spectroscopy of N2 O between 5696 and 5910 cm −1 . 3326 lines assigned to 50 bands of five N2 O isotopologues in natural abundance. 26 of the 31 bands of the main isotopologue, 14 N2 16 O, are newly reported. The spectroscopic parameters of the upper levels are derived from a band-by-band fit. Intra- and inter-polyad perturbations identified for a number of bands. Abstract: In spite of being a greenhouse gas with a large global warming potential, the absorption spectrum of nitrous oxide in the near infrared is insufficiently characterized. In the present work, the spectral region near 1.74 µm (5696–5910 cm −1 ) is investigated by high sensitivity cavity ring down spectroscopy (CRDS). The noise level of the CRDS spectra corresponds to a typical minimum detectable absorption, α min, below 10 - 10 cm −1 . 3326 transitions are measured and rovibrationally assigned to 50 bands of five nitrous oxide isotopologues ( 14 N2 16 O, 14 N 15 N 16 O, 15 N 14 N 16 O, 14 N2 18 O and 14 N2 17 O) in natural isotopic abundance. The assigned weakest lines have an intensity below 10 −28 cm/molecule. For comparison, only three 14 N2 16 O bands are included in the HITRAN database in the region, with a 2 × 10 −25 cm/molecule intensity cut off. The rovibrational assignments were performed by comparison with predictions performed for each isotopologue in the frame of the effective operator approach. The overall quality of the predictions is satisfactory for line positions. Deviations larger than 0.1 cm −1 are nevertheless noted for 14 N2 16 O and 14 N2 18 O. The spectroscopic parameters of the upper level of the observed bands were derived from the standard band-by-band fit of the measured line positions. A significant number of bands were found to be perturbed by local rovibrational perturbations and in some cases, extra lines due to an intensity transfer could be assigned. The interaction mechanisms and the perturbers were univocally identified on the basis of the effective Hamiltonian model. In particular, interpolyad couplings were evidenced indicating that the polyad version of the effective Hamiltonian has to be extended to include Coriolis and interpolyad anharmonic interactions. No satisfactory modeling of the N2 O line intensities is yet available in the region. The CRDS intensity values derived in this work provide a solid set of measurements for future semi-empirical intensity modeling in the region. Graphical abstract: Image, graphical abstract